American coercive diplomacy towards Iran (Trump administration period) - Al-Barzinji, Dana Ali Salih; Al-Barzinji, Yaqub Mehdi Arif (Journal of Legal and Political Studies, 2020)
This article deals with an essential and vital topic represented by US coercive diplomacy; its foundations, goals, and extent of its success during the Trump Administration's tenure towards Iran, which has not yet ended. It does so via adopting more than one method; most importantly are the descriptive and historical approaches in the study of the variables and realizing the pattern of American coercive diplomacy, as well as the discourse analysis method as a way to analyze some statements or tweets for decision-makers in the both countries (USA and Iran). The tenure of Trump's Administration has witnessed a rapid expansion in adopting the option of coercive diplomacy towards Iran and witnessed a kind of escalation in controversial relations between the two sides; America’s withdrawal from the nuclear agreement with Iran and imposing more economic sanctions on it, as well as airstrikes on vital targets of Iran outside its territory. Although the incident of Qasim Soleimani’s assassination confirms America's willingness to use military power in a limited manner to hit selected targets coercive diplomacy remains a priority and a strategic choice. There have been a number of goals behind this diplomacy; such as political and security goals which related to the economic and strategic interests of the United States in the Middle East, the most important of which are consolidating American hegemony and influence and defeating Iran's regional hegemony in the region i.e. preserving its strategic allies (Israel and the Gulf states), ensuring the flow of energy. American coercive diplomacy towards Iran wasn't successful in achievingits goals completely. The extent of the success of US coercive diplomacy towards Irandepends, to a large extent, on the degree to which states stand with it on the one hand and the extent of Iran's resistance to this diplomacyon the other hand.
Keywords: US; America; coercive diplomacy; Iran; Trump,Economic Sanctions